DAMPAK POSITIF SOSIAL MEDIA DALAM PEMBENTUKAN KARAKTER ISLAMI - Fadillah, Ahmad Arif; Putri, Lisa Denanda; Malika, Delfina Laura; Khoirunnisa, Siti; Mutiara, Rahma; Jihan, Nabilah Nur; Khoirunnisa, Elita; Nur’aini; Melati, Suci; Ramadhani, Hardika (Transpublika Publisher, 2022)
The development of social media is getting more and more advanced day by day. The development of social media, which is increasingly popular with everyone, has reached its heyday and is used in several kinds of fields, namely in the field of education and religion (Islam). Social media is used to help students' learning activities. However, the use of social media in students fosters an impact, whether it is a good impact or a positive or negative impact. Social media is a social structure that comes from individuals and organizations that are bound by the similarity of their users. Social media is an online media (online media) that is used as a means of socializing online on the internet. On social media, users can interact with each other, communicate, share networking and various other activities online. Social media was created to qualify humans because humans are social creatures, created to socialize. Because the development of the times is increasingly advanced, the main purpose of which is to facilitate users or users of social media so that they can connect with someone in one country, even between countries and between continents practically and do not waste time or make it easier for users to socialize. However, in today's modern era, social media does not only function as usual, it turns out that social media has an influence on the character education of the students who use it. Whether it's a positive influence or a negative influence such as showing off on social media. Talking about strengthening the character building of students through character education in the context is now very relevant to overcome the moral crisis that is happening in schools and colleges. Admittedly or not recognized there is currently a real crisis that is worrying in the school environment involving students.